An elastic-wave-based full-wavefield imaging method for investigating defects in a high-speed railway under-track structure. Issue 77 (October 2015) - Che, Ailan; Tang, Zheng; Feng, Shaokong
Abstract: In geotechnical engineering, defect detection for concrete structure can be simplified as a multi-layered media problem in most cases. The types of defects are mainly identified as cracks inside the concrete, interlaminar peeling, and loose bedding voids. The study of the wave propagation phenomenon in multi-scale layered media and the effects on defects merits investigation. The present research focuses first on the analysis of this phenomenon using numerical methods. The wave propagation characteristics of the multi-layered model with defects are assessed with dynamic FEM analyses under three-dimensional conditions. The analysis is obtained in the time domain and allows the consideration of multiple wave reflections between layers. Based on this analysis, a full-wavefield imaging detection method is developed and then applied to reveal the defects in the under-track structure of a high-speed railway. This testing system integrates the point-source/point-receiver scheme with the multi-directional imaging technique to achieve an effect analogous to that achieved with scanning. It is equipped with an impacting hammer, a series of three-component velocity transducers and a signal capturing unit. To evaluate the feasibility of this system for detecting defects in the under-track structure of the high-speed railway, a full-scaled high-speed railway model test with pre-setting defection is conducted. The data are analyzed according to characteristics of waveform and wave energy. The average amplitude is used to evaluate the defect area. It is concluded that the full-wavefield imaging detection method exhibits high potential for inspecting the defects of the under-track structure of high-speed railways by imaging. Highlights: A full-wavefield imaging detection method is developed. Wave propagation phenomenon in multi-scale layered media is discussed using FEM. A full-scaled model test of high-speed railway with defects is conducted. The average amplitude of waveform is used to evaluate the defect area.